Universities vs. research institutes? overcoming the Soviet legacy of higher education and research - Lovakov, A; Chankseliani, M; Panova, A (Springer, 2022)
Universities and non-university research institutes have been recognised as two key sectors producing research globally. The Soviet model of research organisation included a large network of research institutes, affiliated with the USSR Academy of Sciences and republican academies, as well as industry research institutes, affiliated with sectoral ministries. Universities played a minor role in research. Post-Soviet higher education and research systems went through reforms in the last three decades which led to changes in the patterns of knowledge production. This study offers an overview of the reforms and a bibliometric analysis of 319410 publications in journals indexed in the Web of Science database to examine how selected post-Soviet countries have overcome the Soviet legacy of organisational separation of higher education and research. While universities now produce the bulk of research output in selected countries, in the majority of national contexts, Academies of Sciences continue to be important players in research.